2012
DOI: 10.1105/tpc.112.099002
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Inhibition of the 2-Oxoglutarate Dehydrogenase Complex in Tomato Demonstrates Its Importance for Plant Respiration and during Leaf Senescence and Fruit Maturation

Abstract: Transgenic tomato (Solanum lycopersicum) plants expressing a fragment of the gene encoding the E1 subunit of the 2-oxoglutarate dehydrogenase complex in the antisense orientation and exhibiting substantial reductions in the activity of this enzyme exhibit a considerably reduced rate of respiration. They were, however, characterized by largely unaltered photosynthetic rates and fruit yields but restricted leaf, stem, and root growth. These lines displayed markedly altered metabolic profiles, including changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 136 publications
7
65
0
Order By: Relevance
“…Several studies of mutants impaired in the TCA cycle and photorespiration provided experimental evidence that the contents of pyridine nucleotides and their respective ratios are rather stable and do not undergo large changes in response to mutations within both pathways (Queval et al, 2007;van der Merwe et al, 2009;Araújo et al, 2012). However, despite reports on direct mutations of the TCA cycle and photorespiration, it was shown that impairments of the mitochondrial electron transport chain or associated components such as alternative mitochondrial NAD(P)H dehydrogenases result in considerable alterations in pyridine nucleotide contents (Liu et al, 2008;Wallström et al, 2014).…”
Section: Overexpression Of Mtlpd Strongly Shifts Pyridine Nucleotide mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of mutants impaired in the TCA cycle and photorespiration provided experimental evidence that the contents of pyridine nucleotides and their respective ratios are rather stable and do not undergo large changes in response to mutations within both pathways (Queval et al, 2007;van der Merwe et al, 2009;Araújo et al, 2012). However, despite reports on direct mutations of the TCA cycle and photorespiration, it was shown that impairments of the mitochondrial electron transport chain or associated components such as alternative mitochondrial NAD(P)H dehydrogenases result in considerable alterations in pyridine nucleotide contents (Liu et al, 2008;Wallström et al, 2014).…”
Section: Overexpression Of Mtlpd Strongly Shifts Pyridine Nucleotide mentioning
confidence: 99%
“…To circumvent this problem, the relative levels of metabolite pairs for compartment specific reactions are often analyzed (Queval et al, 2007;Vivancos et al, 2011;Araújo et al, 2012). Taking this indirect approach and in light of the above-mentioned reports, it seems likely that increases in the NAD + /NADH ratios, as found in mtLPD overexpressors, indicate that the NADH amounts mainly generated through the increased GDC and, to a lesser extent, TCA cycle activity are directly used by the mitochondrial electron transport chain to support ATP production, as reflected in the increased amounts of ATP found in mtLPD overexpression lines (Table 1).…”
Section: Overexpression Of Mtlpd Strongly Shifts Pyridine Nucleotide mentioning
confidence: 99%
“…The next reaction of the cycle that was catalyzed by the 2OG dehydrogenase complex (OGDHC) represents a metabolic branch point connecting 2OG (and the TCA cycle) with nitrogen assimilation with 2OG either being irreversibly degraded by the OGDHC or providing carbon skeletons for nitrogen assimilation. OGDHC is allosterically regulated in response to second messengers and metabolic indicators, such as Ca 2 + , ATP/ADP, NADH/ NAD + , and thiamine pyrophosphate (11). The subsequent enzyme of the cycle, succinyl CoA ligase (ScoAL), is feedback inhibited by intermediates of the pathway of porphyrin biosynthesis as well as competitively inhibited by malonate in the reverse direction but is activated by 2OG and inhibited by both citrate and isocitrate and all downstream intermediates of the TCA cycle when assayed in the forward direction (331).…”
Section: Mitochondrial Contribution To Energy Metabolism-respirationmentioning
confidence: 99%
“…To link these results with the transcriptome data, we found that GRN5 was enriched for genes encoding tricarboxylic acid cycle enzymes and included malate dehydrogenase, citrate synthase, and citrate lyase. In tomato, inhibition of 2-oxoglutarate dehydrogenase results in decreased respiration and increased accumulation of oxoglutarate and succinic acid but no difference in fruit size or biomass (Araújo et al, 2012). In contrast, inhibition of succinate dehydrogenase leads to increased photosynthate assimilation and fruit biomass (Araújo et al, 2011).…”
Section: Comparison Between Metabolite and Transcriptome Profiling Inmentioning
confidence: 99%